Endoscopic management and follow‐up of patients with a submucosal esophageal adenocarcinoma. Issue 5 (1st June 2018) - Künzli, HT; Belghazi, K; Pouw, RE; Meijer, SL; Seldenrijk, CA; Weusten, BLAM; Bergman, JJGHM
Abstract : Introduction: The risk of lymph node metastases (LNM) in submucosal esophageal adenocarcinoma (EAC) patients is subject to debate. These patients might be treated endoscopically if the risk of LNM appears to be low. Objective: The objective of this article is to evaluate the outcome of patients who underwent an endoscopic resection (ER) and subsequent endoscopic follow‐up for a submucosal EAC. Methods: All patients who underwent ER for submucosal EAC between January 2012 and August 2016 and were subsequently managed with endoscopic follow‐up were retrospectively identified. Primary outcome was the number of patients diagnosed with LNM; secondary outcomes included intraluminal recurrences. Results: Thirty‐five patients (median age 68 years) were included: 17 low‐risk (submucosal invasion <500 microns, G1–G2, no lymphovascular invasion (LVI)), and 18 high‐risk (submucosal invasion >500 microns, and/or G3–G4, and/or LVI, and/or a tumor‐positive deep resection margin (R1)) EACs. After a median follow‐up of 23 (IQR 15–43) months, in which patients underwent a median of six (IQR 4–8) endoscopies and a median of four (IQR 2–8) endoscopic ultrasound procedures, none of the included patients were diagnosed with LNM. Five (14%) patients developed a local intraluminal recurrence a median of 18 (IQR 11–21) months after baseline ER that were treated endoscopically. Conclusions: In 35 patients with a submucosal EAC, no LNM were found during a median follow‐up of 23 months. Endoscopic therapy may be an alternative for surgery in selected patients with a submucosal EAC.